DSC722: Research Methodology / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2020)
Data Science is a multidisciplinary field involving database technology, computer science, mathematics, statistics, operations research, and information science for knowledge discovery in large databases. This course aims to provide the necessary scientific knowledge for researching the field of data science. The syllabus is designed to facilitate students to manage their research projects successfully. The topics of specific areas and trends in data. The areas include business intelligence, machine learning algorithms, big data analytics, and optimization and decision support systems. Students will learn innovative ways of harnessing data to transform knowledge and optimize processes in the 21st century.